Hubungan Paritas dan Dukungan Keluarga dengan Keteraturan Konsumsi Tablet Tambah Darah di Wilayah Kerja Puskesmas Sei Bejangkar Kecamatan Sei Balai Kabupaten Batu Bara Tahun 2023 - Ariska Fauzianty; Siska Afriani Br Barus; Nova Isabella Mariance Br Napitupulu (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Background: Anemia is a global health problem where 40% of pregnant women in the world experience anemia. To prevent iron deficiency, pregnant women need adequate iron intake, one of which is regular consumption of blood supplement tablets. Factors that influence pregnant women in consuming blood supplement tablets are parity and husband's support. Objective: to determine the relationship between parity and family support with the regularity of blood supplement tablet consumption. Research method: This study used a descriptive correlation design with a cross sectional approach. Data analysis used the Chi Square test method. This study consisted of 52 people. Research results: Most of them received family support, 22 people (57.7%), almost all of the grand multipara respondents, 46 people (88.5%), and most of them did not regularly consume blood supplement tablets, 31 people (59.6% ). The results of the chi square test showed that there was a significant relationship between family support and parity and regular consumption of blood supplement tablets. Conclusion: Midwives are expected to place more emphasis on counseling by involving families regarding how to consume blood supplement tablets, especially drinks that can block iron absorption, risk factors for anemia, causes of anemia and treatment of anemia during pregnancy.